Scaffold Optimisation of Tetravalent Antagonists of the Mannose Binding Lectin. Issue 11 (15th January 2016) - Goti, Giulio; Palmioli, Alessandro; Stravalaci, Matteo; Sattin, Sara; De Simoni, Maria‐Grazia; Gobbi, Marco; Bernardi, Anna
Abstract: Antagonists of mannose binding lectin (MBL) have shown a protective role against brain reperfusion damage after acute ischemic stroke. Here we describe the design and streamlined synthesis of glycomimetic MBL antagonists based on a new tetravalent dendron scaffold. The dendron was developed by optimisation of a known polyester structure previously demonstrated to be very efficient for ligand presentation to MBL. Replacement of a labile succinyl ester bond with a more robust amide functionality, use of a longer and more hydrophilic linker, fast modular synthesis and orthogonal functionalisation at the focal point are the main features of the new scaffold. The glycoconjugate constructs become stable to silica gel chromatography and to water solutions at physiological pH, while preserving water solubility and activity in an SPR assay against the murine MBL‐C isoform. Higher‐order constructs were easily assembled, as demonstrated by the synthesis of a 16‐valent dendrimer, which leads to two orders of magnitude increase in activity over the tetravalent version against MBL‐C. Abstract : Novel dendrons for multipresentation : Water soluble, tetravalent glycodendrons that perform as powerful mannose‐binding‐lectin (MBL) antagonists are described. The stable scaffold adopted is a versatile tool for nested‐layer multipresentation, which enabled the preparation of higher valency antagonists. All the constructs were tested as MBL‐C antagonists by a surface‐plasmon‐resonance assay and showed binding with IC50 values in the low micromolar range.